Governing cross-border healthcare in mainland China: a scoping review of national policies from 2002 to 2022 - Xiang Yan; Zixuan Han; Pengpeng Ye; Anthony Gar-On Yeh; Xiaoping Xu; Anne W.M. Lee; Kenneth M.C. Cheung; Peng Gong; Shenjing He (Elsevier, 2024)
Summary: This study reviews national-level policies regulating cross-border healthcare in mainland China after it acceded to the World Trade Organization (WTO). Policy documents from official websites of the State Council and 19 ministries were screened, from which 487 policy documents were analyzed. WTO's five modes of trade and WHO's six building blocks of healthcare system were used to guide the analysis of policymaking patterns, charting of policy evolution process, identification of key policy areas, differentiation of 29 detailed policy themes, and identification of major countries/regions involved in cross-border healthcare. The findings lead to four policy recommendations: (1) to establish a national-level committee to govern cross-border healthcare, (2) to build an information system to comprehensively integrate various information on cross-border healthcare consumption and provision, (3) to take more proactive policy actions in healthcare internationalization, and (4) to carry out reform experiments in key sub-national regions to fully explore various possibilities in developing and regulating cross-border healthcare.